KETIKA MEDIA MENJADI HAKIM: Studi Kritis Pemberitaan LGBT di Harian Republika - Oktaviani, Dahlia Sari (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
Mass media has the ability to construct a reality that can represents a person or a particular idea in its news. It is done to lesbian, gay, bisexual, and transgender (LGBT), Republika newspaper is an example that represents LGBT in its news. This study used a qualitative method to see how the Republika represents LGBT. This study uses critical discourse analysis of Fairclough to see how LGBT represented and what contexts which affect it. By doing text analysis, search documents, and literature, author notes that the Republika represents LGBT as a people who deviate from religion and considered a disease that is having psychiatric disorders. Text analysis results showed discrimination that raises principles of journalism violation because media is just pursuing market interests.